(3JhVjM GdcdGe aj TQM TQGFY GdESdGes - (3eMeO Hf YHO Gddg Hf eMeO Hf CMeO Hf eXaQ GdfLaj,J (B1322 (3g` s ((3eMeO Hf eMeO MSfi Hf eMeO GdeXaQ s)
(3ChdgG (B:s
(3hHYO agPG GdcJGH GdeSei HJhVjM GdcdGe bd Sdeg Gddg JYGdi cJGH GdWgGQI s
(3BNQgG (B:s
(3dhcGf GdGNJHGQ HYO GdHdhZ adG jfHZi GdCTcGd ai UMI GdYbO s
(3GdfGSN gh MajO GdeDdas
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3abg GdePGgH GdCNQis